The prognostic value of granulocytes in patients with hodgkin lymphoma - عيسى, بتول; فراس حسين ,; رمال أسعد, (Latakia University Journal -Medical Sciences Series, 2024)
Background: Hodgkin lymphoma has become a curable malignancy. Most of the patients can achieve complete remission. However, a lot of them may be (under or over) treated. It is important at diagnosis to determine the prognosis accurately. Inflammation biomarkers such as leukocytes, neutrophils and lymphocytes correlated with high mortality rates in solid tumors and lymphomas. ANC and NLR at diagnosis are prognostic factors for survival in solid tumors and DLBCL. ALC is an important prognostic factor in Hodgkin lymphoma. Aim: Studying the effect of pre-treatment granulocytes count, pre-treatment neutrophils to lymphocytes ratio and the International Prognostic Score on overall survival (OS) and progression-free survival (PFS) for 18 months in patients with Hodgkin lymphoma. Patients and methods: A prospective study include 80 Hodgkin lymphoma patients newly diagnosed in chemotherapy department at Tishreen University Hospital during 2020-2021.Patients were subjected to routine hematological examinations. IPS was assayed. We assessed the prognostic value of ANC, NLR and IPS in patients with Hodgkin lymphoma through a study of overall survival OS, progression-free survival PFS for 18 months. Results: The study sample included 80 patients with Hodgkin lymphoma, the high ANC associate with bad prognosis, eosinophils count and basophils count had no statistical importance for prognosis. The mean OS and PFS for 18 months were respectively 17.1 and 16.96. The OS rate was 91.3% and the PFS rate was 86.25. Patients with ANC ≥ 8000 had a worse OS and PFS compared to those with ANC < 8000 for 18 months with an HR of 4 and 7 respectively. Patients with NLR ≥ 4.3 had a worse OS and PFS compared to those with NLR < 4.3 for 18 months with an HR of 5 and 9 respectively. Patients with IPS ≥ 4 had a worse OS and PFS compared to those with IPS < 4 for 18 months with an HR of 16 and 7 respectively. Conclusions: High ANC, IPS and NLR can be important prognostic factors, which correlated with bad prognosis in patients with Hodgkin lymphoma.